2009
DOI: 10.1007/s00277-009-0850-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and anemia: a cross-sectional study

Abstract: Vitamin D has been suggested to have an effect on erythropoiesis. We sought to evaluate the prevalence of anemia in a population of individuals with vitamin D deficiency compared with those with normal levels in a population of a large integrated healthplan. A cross-sectional analysis in the period 1 January 2004 through 31 December 2006 of subjects with documented concurrent levels of 25-hydroxyvitamin D and hemoglobin were evaluated. Vitamin D deficiency was defined as <30 ng/mL and anemia was defined as a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
155
3
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(180 citation statements)
references
References 21 publications
(25 reference statements)
10
155
3
5
Order By: Relevance
“…Normalization of levels of vitamin D in these tissues can provoke an adequate amount of substrate for the extra-renal hydroxylases, and these high concentrations of 1. 25 (OH) 2 D in hematopoietic tissues could directly activate precursor erythroid cells [22]. There are authors who postulate that the administration of 25(OH)D is more advantageous for improving anemia in patients with Patients with Chronic Kidney Disease renal insufficiency than 1.25(OH) 2 D administration; this is achieved by administering substrate to the bone marrow to synthesize 1.…”
Section: Discussionmentioning
confidence: 99%
“…Normalization of levels of vitamin D in these tissues can provoke an adequate amount of substrate for the extra-renal hydroxylases, and these high concentrations of 1. 25 (OH) 2 D in hematopoietic tissues could directly activate precursor erythroid cells [22]. There are authors who postulate that the administration of 25(OH)D is more advantageous for improving anemia in patients with Patients with Chronic Kidney Disease renal insufficiency than 1.25(OH) 2 D administration; this is achieved by administering substrate to the bone marrow to synthesize 1.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic lead levels can impair the synthesis of the most important Vitamin D metabolite, dihydroxy Vitamin D (Calcitriol), by inhibiting renal absorption [5]. Till date only one published study has examined the relationship between Vitamin D deficiency and anemia, and has found positive association between the two in adults [6].…”
Section: Introductionmentioning
confidence: 99%
“…Only one published study to date has examined the relationship between vitamin D deficiency and anaemia (5) , and found a positive association between the two in adults. To our knowledge, this has not yet been studied in children.…”
mentioning
confidence: 99%